2013
DOI: 10.1037/a0026248
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional nature of perceived barriers: Global versus practical barriers to HPV vaccination.

Abstract: Objective Perceived barriers are one of the strongest determinants of health behavior. The current study presents a novel conceptualization of perceived barriers by testing the following hypotheses: (a) perceived barriers are multidimensional and thus should cluster into distinct factors; (b) practical barriers should be salient for individuals intending to engage in a particular health behavior, whereas global barriers should be salient for individuals not intending to enact the behavior; and (c) whereas glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 43 publications
8
74
1
Order By: Relevance
“…Perceived barriers included vaccine cost and concerns about vaccine safety and side effects. Cost was not combined with safety/side effects concerns into a single latent factor because items reflected distinct barriers [32]. Whether a doctor or other health care provider had ever recommended the HPV vaccine served as a cue to action.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived barriers included vaccine cost and concerns about vaccine safety and side effects. Cost was not combined with safety/side effects concerns into a single latent factor because items reflected distinct barriers [32]. Whether a doctor or other health care provider had ever recommended the HPV vaccine served as a cue to action.…”
Section: Methodsmentioning
confidence: 99%
“…This issue is not unique to Australia as a previous study from the US also reported the cost of the HPV vaccine as being a barrier to its uptake in young adult women [26]. Cost modelling studies have also shown that the cost benefit of HPV vaccination becomes less favourable with increasing age [13].…”
Section: Discussionmentioning
confidence: 99%
“…While it is crucial to vaccinate those at high risk, it is also vital to focus on young adults who have not initiated sexual activity as this group may benefit most from vaccination. Further research is needed to examine how to increase vaccination rates among those who are not sexually active, as they may view HPV vaccination as unnecessary 29 .…”
Section: Discussionmentioning
confidence: 99%